Corpus callosum hypersignals and focal atrophy: Neuroimaging findings in globular glial tauopathy type I. (12th September 2021) - Keller, Jiri; Kavkova, Anna; Matej, Radoslav; Cséfalvay, Zsolt; Rusina, Robert
Abstract: Background and purpose: Globular glial tauopathies (GGTs) have heterogeneous presentations; little evidence regarding typical clinical and magnetic resonance imaging (MRI) presentations are available. Methods: We retrospectively assessed MRIs from three postmortem‐confirmed GGT cases, in two patients with atypical progressive aphasia and one with corticobasal syndrome. Results: We suggest that four principal concomitant MRI findings characterize GGT type I: a sagittal callosal hyperintense band, marked focal callosal atrophy suggesting white matter degeneration originating in cortical areas responsible for symptoms (anterior atrophy in predominantly language manifestations and posterior atrophy in predominantly apraxia), periventricular white matter lesions, and mild‐to‐moderate brain stem atrophy. Conclusions: We observed four concomitant MRI abnormalities in patients with atypical dementia, parkinsonism, and late incomplete supranuclear gaze palsy. Two patients had atypical progressive aphasia and one had corticobasal syndrome. Abstract : The primary goal of our submission is to make available previously unpublished magnetic resonance imaging (MRI) findings in globular glial tauopathy type I (GGT), a recently discovered rare tauopathy for which limited evidence is available regarding typical clinical and MRI findings. We observed four concomitant MRI abnormalities in patients with atypical dementia, parkinsonism, and late uncomplete supranuclear gaze palsy, with autopsy‐proven GGT.